(untitled) (Scientia Agricola, 2019)
The Atlantic Forest is one of the most important and yet the most devastated Brazilian biome, occupying in the past the majority of the East Atlantic Coast. Therefore, a detailed knowledge of the soils near the coastal line influenced by this biome is essential for land use and management of these environments. The aim of this study was to acquire a deeper knowledge of the chemistry, mineralogy and genesis of soils in two micro-watersheds of the Atlantic Forest Biome. Eight soil profiles were sampled and described along one transect. Both young and more developed soils exhibit low fertility and low Fe2O3 content. The Oxic Dystrudepts are less dystrophic than the other soils studied and exhibit greater availability of K+, due to the mixing of weathered material and primary minerals. Transitions from shallow to deep soils are more common in rejuvenated landscapes. All soils are kaolinitic (Kt), with low levels of goethite (Gt) and hematite (Hm), and contain secondary 2:1 minerals such as mica (Mi) and, in the youngest soils, hydroxy-interlayered vermiculite (HIV) and interstratified mica-hydroxy-interlayered vermiculite (MiHIV). The widespread presence of gibbsite (Gb) in soils, including the Lithic Udifolist, indicates high rates of both pedogenesis and morphogenesis. The gibbsite showed good crystallinity suggesting that climate, terrain and good drainage favored its formation and stability.